Corrosão na geratriz superior do duto (“Top of Line Corrosion – TLC”): uma nova abordagem dos principais mecanismos - Carvalho, Sheyla Santana de (2019)
This work presents a broad experimental and theoretical approach of the condensation and corrosion phenomenon in "Top of line Corrosion" under CO2 environments in conditions of non- film formation (Fe2CO3 or other protective films as corrosion process result). For this, an integrated corrosion cell was developed capable of monitoring the key parameters of this type of corrosion. The condensation rates (WCR) were compared through the theoretical model proposed by Mohammed (2018) allowing an indirect verification of the experimental apparatus in this sense. A cofiguration of Mini-electrodes was adapted to the cell for continuous electrochemical measurements of corrosion by means of integrated analysis of Linear Resistance Polarization-RPL, Electrochemical Impedance Spectroscopy-EIS and Potentiodynamic curves (Tafel). The LPR was monitored for 20 hours and then the average of corrosion rate was compared to those obtained by mass loss under the same conditions in order to validate and measure the accuracy of the methodology used. Finally, a systematic study of TLC corrosion in the API 5LX65 steel compares and analyzes the effects of surface temperature and condensation rate.